Currency crises, monetary union and the conduct of monetary policy : A debate among leading economists - Zak, Paul J.; Claremont Graduate University (Cheltenham, UK ; Northampton, MA, USA : E. Elgar Pub., 1999)
A book of debate and analysis by some of the world's most eminent economists on 'unsolved' problems relating to the international monetary system, economic growth and monetary policy. This volume will be of interest to specialists in international monetary economics, and to undergraduate and graduate students, and members of the general public who seek a clearer understanding of current economic issues and solutions to economic problems
"Debate ... held at Claremont Graduate University in Claremont, California, March 23-25, 1997"--P. 1.
Includes bibliographical references (p. 131) and index.
oif 25/07/16,opc 29/09/16, rua 20/10/16
Loans
Keywords: Monetary policy; Monetary unions; International Finance; Financial crises; Currencies crises